‘Grow For It!’: School-based Intervention to reduce adolescents’ school stress and increase learning and motivation - Andre, Lucija (2025)
This study introduced and evaluated ‘Grow for it!’, a school-based multicomponent intervention designed to enhance adolescents’ Future Time Perspective (FTP) and Growth Mindset (GM) to reduce school stress and improve learning and motivation. A total of 323 Dutch students were randomly assigned to the intervention or control group. The intervention group showed a significant decrease in test anxiety over time, and reported higher FTP, learning investment, GM, and intrinsic motivation at post-test. However, these effects did not persist longitudinally, limiting evidence of the intervention’s overall effectiveness. Nevertheless, our study provided valuable insights into the combined potential of FTP and GM in influencing academic outcomes and highlighted the need for more research about the role of positive adaptive beliefs.